Molecular targeting of liposomal nanoparticles to tumor microenvironment - Zhao G (Dove Medical Press, 2012)
Gang Zhao,1,2 B Leticia Rodriguez21Institute of Materia Medica, Shandong Academy of Medical Science, Shandong, China; 2Pharmaceutics Division, College of Pharmacy, The University of Texas at Austin, Austin, TX, USAAbstract: Liposomes are biodegradable and can be used to deliver drugs at a much higher concentration in tumor tissues than in normal tissues. Both passive and active drug delivery by liposomal nanoparticles can significantly reduce the toxic side effects of anticancer drugs and enhance the therapeutic efficacy of the drugs delivered. Active liposomal targeting to tumors is achieved by recognizing specific tumor receptors through tumor-specific ligands or antibodies coupled onto the surface of the liposomes, or by stimulus-sensitive drug carriers such as acid-triggered release or enzyme-triggered drug release. Tumors are often composed of tumor cells and nontumor cells, which include endothelial cells, pericytes, fibroblasts, stromal, mesenchymal cells, innate, and adaptive immune cells. These nontumor cells thus form the tumor microenvironment, which could be targeted and modified so that it is unfavorable for tumor cells to grow. In this review, we briefly summarized articles that had taken advantage of liposomal nanoparticles as a carrier to deliver anticancer drugs to the tumor microenvironment, and how they overcame obstacles such as nonspecific uptake, interaction with components in blood, and toxicity. Special attention is devoted to the liposomal targeting of anticancer drugs to the endothelium of tumor neovasculature, tumor associated macrophages, fibroblasts, and pericytes within the tumor microenvironment.Keywords: tumor microenvironment, endothelium, neovasculature, tumor-associated macrophages, cationic liposomes, ligand- or antibody-mediated targeting